In Vitro Anti-tumor Immune Response Induced by Dendritic Cells Transfected with Recombinant Adenovirus Carrying Mutant K-ras Genes - 赵峰 周清华 陆燕蓉 覃扬 张洁 李劲松 王建军 (Journal of Huazhong University of Science and Technology. Medical sciences, 2005)
Summary： The specific anti-tumor immune response induced by mouse bone marrow dendritic cells （DCs） lransfected with recombinant adenovirus carrying mutant k-ras genes was investighted. DCs were generated from mouse bone marrow in the presence of rmGM-CSF （3.3 ng/mL） and rmIL-4 （1.3 ng/mL） and detected by FACS, and then transfecled with the recombinant adenovirus encoding mutant k ras gene. The efficacy of transfection and T cell stimulating activity of DCs were detected. CTL activity of the mice vaccinated with DCs was observed. The resuhs showed thai DCs had dendritic veiled morphology. BmDCs highly expressed B7-1（80%）, B7-2（77%）, MHC Ⅱ （70%）, CDllc （65%）, CD40 （70%） and CD54 （96%） with FACS, and no significant difference in the expression was observed before and after the transfection （P〈0.05）. The DCs transfeeled by mutant k-ras gene could significantly stimulate lymphoeytes proliferation as compared with those transfeeted by Ad e or non-modified DCs （P〈0.05）. DC vaccine transfected by mutant k-ras gene could induce CTL activity against Lewis lung cancer, but not against B16. The specific eytotoxicity against Lewis lung cancer in Ad-k-ras/12-transdueed DC group was signifieantly higher than those in the control, vector and non transfeeted DCs groups （P〈0.05）. It was concluded that special antitumor response could be induced by DCs transfected with recombinant adenovirus carrying mutant k-ras genes.